Correction: Two-dimensional porous nickel oxalate thin sheets constructed by ultrathin nanosheets as electrode materials for high-performance aqueous supercapacitors. Issue 18 (29th April 2020) - Zhao, Chenglan; Jiang, Yuqian; Liang, Shunfei; Gao, Fang; Xie, Li; Chen, Lingyun
Abstract : Correction for 'Two-dimensional porous nickel oxalate thin sheets constructed by ultrathin nanosheets as electrode materials for high-performance aqueous supercapacitors' by Chenglan Zhao et al., CrystEngComm, 2020, DOI: ; 10.1039/d0ce00268b .